2005
DOI: 10.1007/s11160-006-0002-y
|View full text |Cite
|
Sign up to set email alerts
|

Parent–egg–progeny Relationships in Teleost Fishes: An Energetics Perspective

Abstract: page 399

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
274
4
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(299 citation statements)
references
References 127 publications
17
274
4
4
Order By: Relevance
“…Variations in fecundity among the same and different species are common phenomenon and differ from year to other Najim et al (2012). Many factors could be influenced fecundity; length, weight, age, food abundance, environmental factors and fish status (Lambert et al, 2003;Kamler, 2005). However, there is compatible with our finding in the present work in general trends and with the previous studies on represented species (Al-Selah et al, 2010;Oymak et al, 2011;Al-Selah et al, 2012;Duman and Gul, 2013).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Variations in fecundity among the same and different species are common phenomenon and differ from year to other Najim et al (2012). Many factors could be influenced fecundity; length, weight, age, food abundance, environmental factors and fish status (Lambert et al, 2003;Kamler, 2005). However, there is compatible with our finding in the present work in general trends and with the previous studies on represented species (Al-Selah et al, 2010;Oymak et al, 2011;Al-Selah et al, 2012;Duman and Gul, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Eggs size is important parameter to success the reproductive cycle of species that strongly associated with maximum size of the species (genetic), physiology, food available and environmental conditions. Caloric value of oocyte yolk which is largely associated of content water, lipids and protein that enables the larvae to pass the critical stage in their life history (Kamler, 2005). Yolked oocyte diameter is largely governed by the natural size of species attained, environmental conditions, reproductive strategy, spawning pattern and parental care (Lambert et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it may be that the principal advantage to the production of large eggs for rocky-shore cichlids lies in the larger size at hatching of the offspring. Larger offspring are likely to be less vulnerable to a certain component of the predator community or vulnerable for a shorter period and be better competitors over food and space (43,44). It has been suggested that there is high predation pressure on young fish in the crowded rocky shores of the African Great Lakes (17).…”
Section: Discussionmentioning
confidence: 99%
“…Low concentrations of this steroid in the plasma of OFs may be related to a reduced reproductive performance of this group (data not shown), since it is known that fish age and size interfere with the reproductive performance by several mechanisms (MARTEINSDOTTIR and STEINARSSON, 1998;BERKELEY et al, 2004;VLADIĆ and PETERSON, 2015), including the gonadal steroid profile (CIERESZKO et al, 1998). In the wild, older females may arrive at spawning areas earlier and spawn before younger females (MARTEINSDOTTIR and STEINARSSON, 1998;KAMLER, 2008). In some cases, as observed for brook trout (BLANCHFIELD and RIDGWAY, 2005), larger females make use of the best areas, with better food resources to the offspring.…”
Section: Discussionmentioning
confidence: 98%